A Robust Voice Activity Detection based on Noise Eigenspace Projection - Ying, Dongwen; Shi, Yu; Soong, Frank; Dang, Jianwu; Lu, Xugang (ISCSLP 2006, 2006)
A robust voice activity detector (VAD) is expected to increase the accuracy of ASR in noisy environments. This study focuses on how to extract robust information for designing a robust VAD. To do so, we construct a noise eigenspace by the principal component analysis of the noise covariance matrix. Projecting noise speech onto the eigenspace, it is found that available information with higher SNR is generally located in the channels with smaller eigenvalues. According to this finding, the available components of the speech are obtained by sorting the noise eigenspace. Based on the extracted high-SNR components, we proposed a robust voice activity detector. The threshold for deciding the available channels is determined using a histogram method. A probability-weighted speech presence is used to increase the reliability of the VAD. The proposed VAD is evaluated using TIMIT database mixed with a number of noises. Experiments showed that our algorithm performs better than traditional VAD algorithms.